Positivities of Knots and Links and the Defect of Bennequin Inequality. Issue 1 (2nd January 2022) - Hamer, Jesse; Ito, Tetsuya; Kawamuro, Keiko
Abstract: We discuss relations among various positivities of knots and links, such as strong quasipositivity and quasipositivity. We give several pieces of supporting evidence for conjectural statements concerning these positivities and the defect of Bennequin inequality. Finally, we determine strong quasipositivity and quasipositivity for knots up to 12 crossings (with two exceptions for quasipositivity).